Implementation of Risk Management in Archive Management at Universitas Islam Negeri Walisongo, Semarang - Soimah Soimah (At-Taqaddum, 2023)
Good and planned archive management will provide significant benefits to the organization. On the other hand, improper archives management will put an organization or institution at risk. Therefore, implementing risk management in archive management is essential to minimize the impact of risks that may arise in archive management. UIN Walisongo Semarang has implemented risk management since 2020. Implementing risk management is one of the components of realizing good university governance. This research aims to determine the extent to which risk management is implemented at UIN Walisongo Semarang and whether the implementation of risk management has positively contributed to improving archive management at UIN Walisongo. This research uses a descriptive-qualitative approach, with case studies on applying risk management in several work units (faculties) and the General Division of UIN Walisongo Semarang. The results of this research show that the implementation of risk management has not been optimal and has not made a positive contribution to archive management at UIN Walisongo because the archive management functions need to function better. In addition, it is due to the lack of archival human resources who understand risk management.